Optimization of dna extraction from orang utan using mitochondrial cytochrome b gene - Lim, Kennedy Chong Ming (Universiti Malaysia Sarawak (UNIMAS), 2011)
This study examines the optimization of DNA extraction from Orang Utans' hair samples. The DNA sequence analyses were carried out using mitochondrial Cytochrome b gene. A total of 8 samples of Orang Utan were used in this study, which were collected from the Matang Wildlife Centre. The methods used were conventional CTAB method and commercial DNA Extraction Kit (Promega). The results showed that extraction was possible using both methods but the DNAs present were contaminated with organic materials. Due to the contaminants and insufficient DNA concentration, optimization of the extracted DNA was not successfully achieved.